Hygrothermal performance of an internally insulated masonry wall: Experimentations without a vapour barrier in a historic Italian Palazzo - Andreotti, Mirco (2022)
This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)